Innovation of porous concrete with ldpe plastic agregate as an eco-friendly solution for sustainable construction - Fauzan, Muhamad Bintang; Shafir, Annisa Fidanta; Meisarohmah, Winda Tsani; Defriadi, Naila Zhafira; Febriansyah, M Andhyka; Arfiansyah, Dimas Surya (2025)
The increasing volume of plastic waste, particularly from food packaging and beverage bottles, has become a significant environmental challenge. One innovative solution to mitigate this impact is the utilization of plastic waste as a construction material, such as in previous concrete. This study aims to evaluate the effect of substituting coarse aggregate with low-density polyethylene (LDPE) plastic waste on the compressive strength of previous concrete. The LDPE content variations used in the mixtures were 10%, 20%, 30%, 40%, and 50% by volume of coarse aggregate, targeting a compressive strength equivalent to Class II quality concrete (16–24 MPa) for precast drainage channels. The mix design was calculated based on the Indonesian National Standard (SNI) 2834:2000, and compressive strength tests were conducted on concrete beams measuring 15 × 15 × 60 cm. The results indicated that the higher the LDPE content, the lower the compressive strength of the concrete. Normal concrete recorded the highest compressive strength at 25.31 MPa, whereas concrete with 50% LDPE substitution only reached 5.47 MPa. Although the strength did not meet Class II standards, mixtures with 10% to 40% LDPE content still fulfilled the requirements for Class I quality concrete, suitable for non-structural applications. Therefore, LDPE plastic waste has potential as an alternative coarse aggregate in environmentally friendly previous concrete.